(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Humans have been traveling for some reason since ancient times. Earlier tourism was limited due to lack of transport facilities. But today the means of transportation has increased to a great extent. Therefore, tourists are seen visiting various tourist places. This helps the local people in their economic development by providing employment. Wadwal is a religious tourist spot five km east of Mohol in Mohol taluka of Solapur district in Maharashtra and it is a neglected tourist spot. This tourist spot does not seem to be developed as it was expected. This a research paper titled “Wadwal A Neglected Religious Tourist Place: A Geographical Study” aims to introduce this religious tourist place to everyone.